Use of Ammonia Semidry Technology for Flue Gas Desulfurization in Coal Power Plants - Volchyn, I.A.; Kolomiyets, O.M. (Science and Innovation, 2024)
The environmental protection legislation of Ukraine and the European Union requires a significant reduction in sulfur dioxide emissions at thermal power plants. Therefore, the need to design, to produce, and to build an installation for flue gas desulfurization in compliance with European best practice. The necessary condition is to determine optimal parameters for variable modes of purifying installation. The article presents the results of numerical modeling of semidry desulfurization plant to bind sulfur dioxide in flue gases coming from the boiler TPP-210A of 300 MW power unit. The desulfurization plant works on the semidry method using ammonium water as sorbent. Upon the results of research, the size of reactor operating area as main part of desulfurization plant has been established, the method for feeding ammonia and water used to prepare the solution and to irrigate flue gas flow has been defined. The consumption rate of ammonia solution and water has been estimated depending on volume of flue gas and water and inlet temperature of gases.